P13.14 Inhibition of extracellular carbonic anhydrases reduces glioblastoma cell invasion. (9th September 2021) - Proescholdt, M; Qiu, Z; Falter, J; Schmidt, N
Abstract: BACKGROUND: Malignant gliomas metabolize glucose preferably by glycolysis which is in accordance with the Warburg effect. This induces a high demand of glucose combined with a significant lactic acid load. The hypoxia-inducible carbonic anhydrase (CA) IX has been shown to moderate the extrusion of hydrogen ions into the extracellular space. Since the acidification of the extracellular environment contributes to host tissue invasion due to activation of proteolytic enzymes, we hypothesized that CA IX plays an important role in malignant glioma Recently, specific small molecule inhibitors of this enzyme have been developed and may provide an innovative strategy for anti - invasive treatment. MATERIAL AND METHODS: Two established and 4 primary GBM cell lines (2 with mesenchymal and 2 with proneural transcriptional profile) were exposed to the CAIX inhibitor U104 under normoxic and hypoxic conditions. Cell toxicity was measured by ATP and crystal violet assay. For invasion assessment, a matrigel invasion chamber system with 8 µm pore size polycarbonate filter was used. CAIX expression was analyzed by quantitative RTPCR and Western Blot. RESULTS: Hypoxia significantly induced CAIX expression in all cell lines. Invasiveness increased significantly under hypoxic conditions in the mesenchymal cells (p < 0.01). Regardless of oxygenation status, the mesenchymal group displayed significantly higher invasiveness compared to the proneural group (p = 0.006). Looking at all cell lines, invasion is significantly inhibited by U104, both under normoxic and hypoxic conditions (p < 0.01). However, while the mesenchymal group showed the highest susceptibility to CAIX inhibition followed by the proneurally differentiated group, the established cell lines were entirely refractory to CAIX inhibition. CONCLUSION: Our data demonstrate that CAIX inhibition can effectively inhibit invasion in malignant glioma cells independent from oxygenation status, however the effects are significantly influenced by cell type specific biological features.